Clinical psychology in haemoglobinopathies: cost effective pathways to funding - Lloyd, Joanne; das Nair, Roshan; Mackinlay, Dot (British Psychological Society, 2013)
This article describes a service evaluation which was used as evidence in a bidfor clinical psychology funding in haemoglobinopathies. We present the approach as a promising framework for securing funding in this difficult financial climate. SICKLE CELL DISEASE (SCD) and thalassaemia are inherited blood disorders that vary significantly in their presentation and treatment but are known collectively as `haemoglobinopathies'. SCD is characterised by an abnormality in the synthesis of normal haemoglobin (De, 2005). In SCD, abnormally shaped haemoglobin are responsible for small vessel blockages which account for several symptoms and complications including acute episodes of pain ('crises'), organ failure and stroke. UK incidence of SCD is estimated to exceed 10,000, making it the most common genetic condition in the UK. It is most commonly diagnosed in African and Caribbean populations. Tha-lassaemia is a chronically recessive inherited blood disorder most commonly diagnosed in Eastern Mediterranean, Asian, and Middle Eastern populations. There are several different types of thalas-saemia, which vary in terms of illness severity and treatment intensity. The main types, alpha thalassaemia and beta thalas-saemia, differ depending on which haemoglobin chain is affected. Beta thalassaemia major is a severe form causing life threatening anaemia which, without medical intervention by regular blood transfusions, is fatal. Psychosocial difficulties are common in haemoglobinopathy populations (Molock & Belgrave, 1994; Vardarki et al., 2004) and neuropsychological difficulties have been widely documented in SCD (Berkelhammer et al., 2007). The importance of clinical psychology input into services for people with SCD and thalassaemia has been recognised (Sickle Cell Society, 2008; 2010; UK Thalassaemia Society, 2008). Indeed, specialist clinical and health psychology services have been developed in other centres including London, Birmingham and Manchester. At the start of this project there was no clinical psychology provision for people with SCD and thalassaemia in the Nottingham area despite a haemoglobinopathy population of approximately 140. To secure local funding in an uncertain climate, a needs assessment was completed, where we provided evidence for a service need and produced a toolkit of materials to facilitate the future post-holder's prompt integration into the service.